Lithofacies, mineralogy, and pore characteristics of Permian marine tuffaceous rocks in the Sichuan Basin - Li, Rong; Xiong, Zhifu; Wang, Zecheng; Xie, Wuren; Li, Wenzheng; Su, Nan (Frontiers in Earth Science, 2023)
Alongside volcanic eruptions in the middle and late Permian, the sedimentary environment and process changed, and the lithofacies and mineralogical characteristics varied conspicuously from the marine sediments in this period. Marine tuffaceous rocks beared strong witness to the marine and volcanic actions in this time. With experimental studies relying on field outcrop, thin section, scanning electron microscope, X-ray diffraction (XRD), mercury injection capillary pressure (MICP) and CT scan, the researchers analyzed the lithology, mineralogy, and pore characteristics of marine tuffaceous rocks. Among the Permian marine tuffaceous sections of the Sichuan Basin, three types of lithofacies were identified, namely tuff, sedimentary tuff, and tuffaceous mudstone. The mineral composition of the tuffaceous section includes quartz, feldspar, carbonate minerals, pyrite, clay, etc. The quartz content varies from 4.0% to 27.3%, with an average value of 13.0%; the feldspar content varies from 0 to 21.2%, with an average value of 9.8%; the carbonate mineral content varies from 8.52% to 53.45%, with an average value of 27.6%; the clay mineral content varies from 0 to 75.3%, with an average value of 44.8%; and the pyrite content varies from 0 to 13.4%, with an average value of 5.8%. The porosity of tuffaceous rocks varies from 2.2% to 8.1%, mostly concentrated in the range from 3% to 7% with an average level of 5.24%. There are mainly shrinkage pores, dissolution pores, intercrystalline pores, and organic pores. In terms of scale, the pores can be classified as micron-scale and nano-scale pores, and in terms of size, they are mainly micropores and mesopores, accounting for up to 92.12%. The pores are concentrated in the tuffaceous section and well interconnected, forming a complex organic-inorganic pore-fracture network system and bedding fractures with even better connectivity. The pores of the tuffaceous section are greatly influenced by lithofacies and mineral composition. The porosities of tuffaceous mudstone, sedimentary tuff and tuff rank downward, with average porosities of 6.5%, 5.09%, and 3.86% respectively. The felsic content is inversely correlated with porosity; the clay content and TOC content are positively correlated with porosity; the pyrite content is also inversely correlated with porosity. The marine tuffaceous section is similar to shale to a certain extent as it has relatively dense lithology, its pores are mainly of micron-scale and nano-scale and mainly include micropores and mesopores. It boasts the hydrocarbon-generating capacity and reservoir performance, serving as both a source rock and a reservoir. As a novel reservoir, the tuffaceous section can form a tight reservoir both generating and depositing gas and featuring source-reservoir paragenesis, lithological reservoir-controlling, and large-area stratified distribution, manifesting a promising future for exploration.